HVDC converter control performance during faults - Devarapalli R.; Pandey R.K. (My University, 2025)
This paper presents a detailed system analysis for HVDC converter controls both at rectifier and inverter terminal. The faults analysis has been carried out for all combinations of AC system strength which includes strong and weak system conditions. It has been observed that the system behaviour at weak inverter AC system conditions is very difficult to recover, however for strong AC system this effect is relatively low. For weak inverter operation the use of STATCOM may be beneficial even during faults. © 2012 Pillay Engineering College.